Indoor America : the interior landscape of postwar suburbia - Vesentini, Andrea, 1985- (Midcentury (Charlottesville, Va.), 2018)
"Cars, single-family houses, fallout shelters, air-conditioned malls-- These are only some of the many interiors making up the landscape of American suburbia. Indoor America explores the history of suburbanization through the emergence of such spaces in the postwar years, ezamining their design, use, and representation. ..."--Publisher's announcement